1968
DOI: 10.1159/000458256
|View full text |Cite
|
Sign up to set email alerts
|

Leucine aminopeptidase et naphtylamidases dans l’épiderme humain

Abstract: Résumé. L’action des naphtylamidases et de la leucine aminopeptidase de l’épiderme est étudiée sur 23 naphtylamides, la leucinamide et la leucyl-glycine au moyen de méthodes fluorométriques, isotopiques et spectrophotométriques. La comparaison avec d’autres tissus est discutée.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1969
1969
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
(7 reference statements)
1
1
0
Order By: Relevance
“…Good agreement with other investigators (Mier & van den Hurk, 1975;Hopsu-Havu & Jansen, 1969) was found for the enzyme characteristics of cathepsin Bi and cathepsin C. The Michaelis-Menten constants of arylamidase correspond well with the value (3-5Xio~*mol/l) found by de Bersaques (1968) for human epidermis, whereas Mier & van den Hurk (1975) reported lower values for guinea-pig epidermis. The results of thermal inactivation of cathepsin Bi are quite similar to those of Ali et al (1967), who found a loss of about 50% of its activity after heating at 52°C for 30 min.…”
Section: Discussionsupporting
confidence: 89%
“…Good agreement with other investigators (Mier & van den Hurk, 1975;Hopsu-Havu & Jansen, 1969) was found for the enzyme characteristics of cathepsin Bi and cathepsin C. The Michaelis-Menten constants of arylamidase correspond well with the value (3-5Xio~*mol/l) found by de Bersaques (1968) for human epidermis, whereas Mier & van den Hurk (1975) reported lower values for guinea-pig epidermis. The results of thermal inactivation of cathepsin Bi are quite similar to those of Ali et al (1967), who found a loss of about 50% of its activity after heating at 52°C for 30 min.…”
Section: Discussionsupporting
confidence: 89%
“…It is not yet clear whether or not the amino acid 2-naphthylamidases are peptidases, as the natural substrates are unknown, though it has been shown that their activities are distinct from those of the peptidases, cathepsins B, Bi, C and D (Barrett & Poole, 1969;McDonald et al, 1970). The fact that two types of amino acid 2-naphthylamidase exist in epidermis, together with the finding that the soluble enzymes, which account for the major portion of the amino acid 2-naphthylamidase activity in pig and human epidermis, do not exhibit Michaelis-Menten kinetics, must put in doubt the values of Michaelis constants previously reported for these enzymes in unfractionated homogenates of epidermis (De Bersaques, 1968;Mier & Van den Hurk, 1975).…”
Section: Pig Epidermismentioning
confidence: 90%